‘Consumer Ethics: The Role of Acculturation in U.S. Immigrant Populations’ - Swaidan, Ziad (Journal of business ethics, 2006)
This study examines the role of acculturation in shaping consumers’ views of ethics. Specifically, it examines the relationships between the desire to keep one’s original culture, the desire to adopt the host culture, and the four dimensions of the Muncy and Vitell (Journal of Business Research Ethics 24(4), 297, 1992) consumer ethics scale. Using two separate immigrant populations – one of former Middle-Eastern residents now living in the U.S. and the other of Asian immigrants in the U.S. – results indicate that those who want to keep their original culture are less tolerant of unethical consumer activities, while those who are more willing to adopt the host culture are more tolerant of these same consumer activities. Furthermore, the immigrants in both studies who are more tolerant of unethical consumer activities are those who are generally somewhat younger and with less formal education. The relationship between gender and consumer ethics was not significant.